2015
DOI: 10.1177/0954008314566434
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun carboxylic-functionalized poly(arylene ether ketone) ultrafine fibers

Abstract: As a high-performance polymer, carboxylic-functionalized poly(arylene ether ketone)s (PCA-PAEK) was electrospun into ultrafine fibers and characterized. To optimize the process, a set of experiments were designed. As a result, the optimum condition was obtained and the polymer concentration was determined as the most important factor. Incidentally, the PCA-PAEK fibers were found to exhibit superabsorbent behavior. In order to investigate processing characteristics, PCA-PAEK fibers fabricated from different sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…It was interesting that the fiber diameter was decreased from 1.692 to 0.814 mm in the immersing process. It has been reported in our previous work 40 that when the concentration of PCA-PAEK was 20%, diffusion process was consistent with the Fickian diffusion mechanism. When liquid contacted with the fiber webs, fibers with bigger diameter were relatively more stable and tended to maintain a constant structure thus preventing additional swelling.…”
Section: Characterizationsupporting
confidence: 86%
See 2 more Smart Citations
“…It was interesting that the fiber diameter was decreased from 1.692 to 0.814 mm in the immersing process. It has been reported in our previous work 40 that when the concentration of PCA-PAEK was 20%, diffusion process was consistent with the Fickian diffusion mechanism. When liquid contacted with the fiber webs, fibers with bigger diameter were relatively more stable and tended to maintain a constant structure thus preventing additional swelling.…”
Section: Characterizationsupporting
confidence: 86%
“…Introduction of −COOH improves the solubility and chemical activity of PAEK. In our previous work, 40 PCA-PAEK has been fabricated into ultrafine fibers and the optimum condition has been confirmed. However, as far as we know, it has never been used as a template to prepare CuO/CdO composite NFs.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…To date, in most of the studies performed, electrospun magnetic nanofibers were often deposited on the collector surface as randomly oriented nonwoven mats, which could be unsatisfactory depending on some of their applications. 14 16 Intense research has demonstrated that aligned nanofiber structures possessing well-controlled porosity 17 can effectively improve the mechanical integrity 18 and show unique electric and magnetic properties. 19 Among the synthesis methods of ordered nanofibers, 20 23 the magnetic-field-assisted electrospinning (MFAES) method has been widely employed due to the advantages of simple equipment, easy handling, large production, and so on.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that when the bath ratio was 1:25 and the alkali concentration was 7.5%, super-absorbent fabric with SR of 343 g/g could be obtained, which exceeded the reported water absorption capacity of commercial superabsorbent bers, super-absorbent poly (arylene ether ketone) bers and super-absorbent cellulose nano bers (Fig. 5c) ( Liu et al 2015, Petroudy et al 2021). But the SR of super-absorbent fabric in this work to normal saline and synthetic urine was only 36 g/g and 30 g/g.…”
Section: Swelling Behavior Of St-sa-paa Gel and Super-absorbent Fabricmentioning
confidence: 86%